2023
DOI: 10.1021/acsami.3c03117
|View full text |Cite
|
Sign up to set email alerts
|

High-Strength Cell Sheets and Vigorous Hydrogels from Mesenchymal Stem Cells Derived from Human Embryonic Stem Cells

Abstract: Natural cell derivates, including cell sheets (CSs) and matrix gels, have opened new opportunities to probe questions in tissue engineering and regenerative medicine. However, the potential of CSs and hydrogels generated by current protocols is still limited by the challenges of heterogeneity and weak mechanical properties. Here, we developed a 21 day long-term serum-free culture system for human embryonic stem cell (hESC)-derived immunity-and-matrix-regulatory cells (IMRCs). The CSs formed with IMRCs (IMRC-CS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…In our study, we noted that the ECM sheet exhibited favorable properties for handling, cutting, and transfer, even after rigorous processing such as vortexing. The resilience was particularly noteworthy as cell-derived sheets often lack mechanical strength due to insufficient thickness. ,, Interestingly, ECM sheets hold significant promise for TE and regenerative medicine applications, potentially serving as a therapeutic option for corneal injuries during wound healing. While hASC-derived ECM sheets have been explored for skin substitutes in wound healing, , the production of ECM sheet during the differentiation of hASCs toward CSKs is a novel approach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, we noted that the ECM sheet exhibited favorable properties for handling, cutting, and transfer, even after rigorous processing such as vortexing. The resilience was particularly noteworthy as cell-derived sheets often lack mechanical strength due to insufficient thickness. ,, Interestingly, ECM sheets hold significant promise for TE and regenerative medicine applications, potentially serving as a therapeutic option for corneal injuries during wound healing. While hASC-derived ECM sheets have been explored for skin substitutes in wound healing, , the production of ECM sheet during the differentiation of hASCs toward CSKs is a novel approach.…”
Section: Discussionmentioning
confidence: 99%
“…Three-dimensional (3D) bioprinting is a state-of-the-art biofabrication technology to manufacture 3D tissue constructs with precise cellular architecture and addresses the substantial need for transplantable tissues and organs. , Therefore, it has gained popularity also in fabricating corneal stromal structures. Previously cornea-specific bioinks have been prepared by using ECM from donor tissue, such as bovine or porcine corneas . Furthermore, cell-derived ECM for corneal TE has been studied with corneal endothelial cells (CECs) as a culture substrate, a corneal endothelium graft, as a model to study cellular dysfunction, or in applications for corneal injury repair. …”
Section: Introductionmentioning
confidence: 99%
“…Until recently, pluripotent cell-derived MSCs were not a popular focus in clinical research, with only a small number of studies exploring this area, despite the wide variety of potential tissues that could be produced. Currently, only three clinical trials involving ESC-derived MSCs [ 81 83 ], and six iPSC-MSCs clinical trials have been reported (Table 2 ) [ 84 , 85 ]. It is important to note that from the six clinical trials, cartilage regeneration through iPSC-MSCs was only addressed in two studies.…”
Section: Main Textmentioning
confidence: 99%